Efficacy and Safety of Acotiamide for the Treatment of Functional Dyspepsia: Systematic Review and Meta-Analysis - Guoguang Xiao; Xiaoping Xie; Juan Fan; Jianjun Deng; Shan Tan; Yu Zhu; Qin Guo; Chaomin Wan (The Scientific World Journal)
Background. There are no treatments with established efficacy for this disorder so far. Aim. To systematically review the efficacy of acotiamide in the treatment of patients with FD. Methods. We searched main electronic databases through November 2013. RCTs evaluating the efficacy of acotiamide versus placebo in FD patients were included. Pooled risk ratio (RR) with 95% confidential interval (CI) was calculated. Results. Six publications including seven RCTs were eligible for inclusion. The summary RR of overall improvement of FD symptoms in patients receiving acotiamide versus placebo was 1.29 (95% CI, 1.19–1.40, P<0.00001; I2=15%). Acotiamide improved the symptoms of patients with postprandial distress syndrome (PDS) (RR, 1.29; 95% CI, 1.09–1.53, P=0.003; I2=0%), and the summary RR for patients with epigastric pain syndrome (EPS) was 0.92 (95% CI, 0.76–1.11, P=0.39; I2=0%). Acotiamide showed a significantly beneficial effect on the elimination of some individual FD symptoms compared with placebo. Adverse events were not significantly different between acotiamide and placebo groups. Subgroup analyses suggested that acotiamide 100 mg three times daily (tid) showed consistent efficacy not only for the overall improvement but also for the elimination of some individual symptoms in FD patients. Conclusions. Acotiamide has the potential to improve the symptoms of patients with FD, particularly of patients with PDS, without major adverse effects. The dosage of acotiamide 100 mg tid might be the appropriate dose in the treatment of FD.